Investigation of diamond deposition on the diamond, silicon and quartz substrates by microwave plasma chemical vapor deposition and Monte Carlo simulations. (10th July 2019) - Reshi, Bilal Ahmad; Kartha, Moses J; Misra, Anuradha; Varma, Raghava
Abstract: In this paper, a growth mechanism of diamond utilizing Microwave plasma chemical vapor deposition (MPCVD) on various substrates alongside Monte-Carlo simulations is presented for the first time. The values of roughness exponent ( α ) have been estimated on diamond, silicon and quartz substrates while as the growth exponent ( β ) is found out through the grown diamond film on a diamond substrate. The roughness exponent has been investigated by evaluating the height-height correlation function for the diamond interface. For diamond, silicon, and quartz the roughness exponent α is found to be 0.42, 0.21 and 0.25 respectively. The value of α  < 0.5 suggests that diamond deposited on silicon and quartz surface has more gagged surface than the diamond deposited on diamond substrates. It has been investigated that the growth exponent β  = 0.45 ± 0.18 is dominated by random deposition with diffusion during the growth process. Monte-Carlo simulation with varying sticking probability p has been carried out in order to reconstruct the interface obtained in experiments. It is found that β decreases with sticking probability p. The interface reconstructed through simulations for this sticking probability shows voids and vacancies during the deposition. Raman spectra and x-ray Photoelectron Spectroscopy (XPS) study confirm the diamond phase of carbon (sp 3 ) is present in the grown films. The diamond grown in the setup used for this study exhibits crystalline nature and long-range order as suggested Raman spectroscopy.